(untitled) (Journal of the College of Basic Education, 2022)
The study aimed to prepare a training program through the use of hyperinflationary exercises (H.S.T) according to the compound movement rhythm (fast-slow) and its effect on muscular endurance and muscle size for advanced bodybuilders. The researchers used the experimental approach for its suitability to the nature of the problem. The research sample consisted of athletes The private halls for bodybuilding, whose number is (8) players, and the research was conducted on one experimental group that underwent a pre-test and a post-test in the variable of muscular endurance and the variable of measuring body circumferences, and the implementation period of the curriculum continued (12) weeks with (3) training units per week After processing the results statistically using the statistical bag (spss), the researchers concluded that hyperinflationary exercises (H.S.T) were performed according to the motor rhythm.